2005
DOI: 10.1136/bjsm.2004.017020
|View full text |Cite
|
Sign up to set email alerts
|

The exercise addiction inventory: a quick and easy screening tool for health practitioners: Table 1

Abstract: Background: Exercise addiction is not routinely screened for probably because available instruments take a long time to administer, their scoring may be complicated, and their interpretation is not always obvious. A new psychometric instrument has been developed that is capable of identifying people affected by, or at risk of, exercise addiction: the exercise addiction inventory (EAI). A preliminary report showed the EAI had good reliability and validity. Objectives: To test further the EAI's psychometric prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
4
16

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(183 citation statements)
references
References 8 publications
7
156
4
16
Order By: Relevance
“…This study is the first investigation of the prevalence of exercise addiction in a Hungarian sample of female aerobic exercisers. We found that 7.5% of the sample were at risk for exercise addiction, which is higher than the previously reported prevalence of exercise addiction (Griffiths et al, 2005;Hausenblas & Symons Downs, 2001;Mónok et al, 2012), but similar to our findings in an earlier study of a similar population of women (Béres et al, 2013).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This study is the first investigation of the prevalence of exercise addiction in a Hungarian sample of female aerobic exercisers. We found that 7.5% of the sample were at risk for exercise addiction, which is higher than the previously reported prevalence of exercise addiction (Griffiths et al, 2005;Hausenblas & Symons Downs, 2001;Mónok et al, 2012), but similar to our findings in an earlier study of a similar population of women (Béres et al, 2013).…”
Section: Discussioncontrasting
confidence: 54%
“…There were no group differences in exercise addiction categories (χ 2 (2) = 0.060, p = .970). A higher proportion of our sample were at risk for exercise addiction than in previously reported international data on physically active populations (Hausenblas & Symons Downs, 2001: 2.5%, χ 2 (1) = 32.416, p < .001; Griffiths, Szabo, & Terry, 2005: 3%, χ 2 (1) = 21.946, p < .001). Prevalence of at-risk for exercise addiction status was higher in our sample than in one recent Hungarian study which used a representative sample of physically active adults (3.2%, χ 2 (1) = 18.806, p < .001), but another study (Béres et al, 2013) reported a 6.7% rate of at-risk for exercise addiction in a similar population; this did not differ significantly from that observed in our study (χ 2 (1) = 0.292, p = .589).…”
Section: Characteristics Of the Samplecontrasting
confidence: 47%
See 1 more Smart Citation
“…67 A questionnaire developed to identify obligatory exercisers may be useful for screening veteran endurance athletes. 68 …”
Section: Risk Stratification For Endurance Athletesmentioning
confidence: 99%
“…In the EDS‐R, all the criteria for dependence in the DSM‐IV were included and linked to exercise behavior. The Exercise Addiction Inventory22 is a short version related to addiction models of understanding exercise. Within this framework, eating disorders are theoretically linked to secondary dependency of exercise.…”
Section: Introductionmentioning
confidence: 99%